Elucidating the role of oxygen vacancies on the electrical conductivity of β-Ga2O3 single-crystals - Narayanan, Maneesha; Shah, Amit P.; Ghosh, Sandip; Thamizhavel, Arumugam; Bhattacharya, Arnab (Applied physics letters, 2023)
The contribution of oxygen vacancies ( V O) to the electrical conductivity of unintentionally doped β-Ga2O3 has been a topic of recent debate. Here, we use a combination of Hall measurements and Raman spectroscopy on as-grown and O2-annealed β-Ga2O3 crystals to investigate the role of V O on electrical conductivity. The annealed samples show a significant decrease in carrier concentration. By comparing the relative Raman shift of individual modes with theoretically calculated contributions of oxygen sites to these modes, we verify the marked reduction of V O in annealed β-Ga2O3 crystals. Furthermore, the IR modes in β-Ga2O3, usually hidden by free carrier absorption, are clearly seen in the annealed sample. The reduction of band tail states as well as free carrier absorption in the annealed samples provides additional evidence for reduced carrier concentration related to V O, making them a key determinant of electrical conductivity in β-Ga2O3.